Exploring of spectroscopic, dielectric, and bioactivity performance of bioglass/sodium alginate-PVP loaded-Amoxicillin/Clavulanic Acid microspheres for bone tissue engineering - Ahmed M. Bakr; Amany M. El Nahrawy; A. M. Mansour; Ali B. Abou Hammad (Scientific Reports)
Abstract This study aims to develop an innovative drug delivery bio-system using bioglass (BIOGLASS) and biopolymers of Sodium Alginate (SA) and polyvinylpyrrolidone (PVP) in microsphere form as a carrier for Amoxicillin/Clavulanic Acid drug. In this work BIOGLASS/SA-PVP and Amoxicillin/Clavulanic Acid loaded BIOGLASS/SA-PVP microspheres (0%, 5%, 10%, and 15%) were synthesized using the ion crosslinking method technique. The fabricated microspheres were analyzed using FT-IR, FESEM/EDX, and XRD confirming the in-vitro examination. XRD and FTIR data demonstrate the effective creation of the apatite layer and the appearance of new apatite peaks at both 605 cm−1 and 565 cm−1, distinguishing the prolonged vibrations associated with the $${\text{PO}}_{4}^{-3}$$ group. SEM images reveal that the prepared bio-beads have a spherical shape, with sizes falling in the micro-scale. The dielectric constant (εʹ), the dielectric loss (εʺ), and the AC conductivity (σ) were slow at the frequency range of 4 Hz to 8 MHz at room temperature. The antibacterial examinations of the fabricated microspheres were performed employing agar diffusion procedure against the clinical pathogens Gram+ and Gram- bacteria. The SBF (simulated body fluid) experiments display the formation of a hydroxy appetite coating on the microsphere’s surfaces that approves their significant bioactivity. Furthermore, antimicrobial results of BIOGLASS/SA-PVP/Amoxicillin/Clavulanic Acid microspheres reveal a notable impact on the antimicrobial performance. The in-vitro tests established that fabricated bio-microspheres are a promising opportunity for bone tissue engineering (substitutes and regeneration), signifying their promise for bone application.